2009
DOI: 10.1161/circulationaha.109.879429
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of MicroRNA-1 and Insulin-Like Growth Factor-1 Signal Transduction Cascade in Cardiac and Skeletal Muscle in Physiological and Pathological Conditions

Abstract: Background-MicroRNAs (miRNAs/miRs) are small conserved RNA molecules of 22 nucleotides that negatively modulate gene expression primarily through base paring to the 3Ј untranslated region of target messenger RNAs. The muscle-specific miR-1 has been implicated in cardiac hypertrophy, heart development, cardiac stem cell differentiation, and arrhythmias through targeting of regulatory proteins. In this study, we investigated the molecular mechanisms through which miR-1 intervenes in regulation of muscle cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
271
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(291 citation statements)
references
References 50 publications
13
271
2
2
Order By: Relevance
“…In addition, a 2-nt substitution in the putative seed sequence of miR-1 was sufficient to significantly reduce miR-1 repressive effect over the 3′-UTR of IGF-1, thus confirming that IGF-1 is a bona fide target for miR-1. During the preparation of this manuscript, and consistent with our findings, it has been reported that miR-1 is able to target IGF-1 in the context of cardiac and skeletal muscle physiology (34,35), which supports our results. To further examine this putative link among miR-1, IGF-1, and progeroid syndromes, we analyzed miR-1 expression levels in cultured fibroblasts derived from patients with HutchinsonGilford progeria syndrome.…”
Section: Resultssupporting
confidence: 92%
“…In addition, a 2-nt substitution in the putative seed sequence of miR-1 was sufficient to significantly reduce miR-1 repressive effect over the 3′-UTR of IGF-1, thus confirming that IGF-1 is a bona fide target for miR-1. During the preparation of this manuscript, and consistent with our findings, it has been reported that miR-1 is able to target IGF-1 in the context of cardiac and skeletal muscle physiology (34,35), which supports our results. To further examine this putative link among miR-1, IGF-1, and progeroid syndromes, we analyzed miR-1 expression levels in cultured fibroblasts derived from patients with HutchinsonGilford progeria syndrome.…”
Section: Resultssupporting
confidence: 92%
“…3, A and B), which is in agreement with previous reports demonstrating a reduction in miR1 expression during cardiac and skeletal muscle hypertrophy (21,22). MicroRNAs act by base pairing to complementary sequences within the 3Ј UTR of target mRNAs and either inhibit translation or promote mRNA degradation.…”
Section: Discussionsupporting
confidence: 91%
“…A cluster of myomiRs including miR1, miR133, and miR206 plays a role in myogenesis and muscle regeneration (19,20). Both miR1 and miR133 were found to be down-regulated in skeletal muscle undergoing hypertrophy and it was proposed that Igf-1 mRNA may be negatively regulated by miR1 in skeletal muscle (21) and cardiac muscle (22). Although it appears that miR1 has a role in regulating muscle hypertrophy through IGF-1, little is known about the role of miR1 in skeletal muscle atrophy.…”
mentioning
confidence: 99%
“…[12][13][14] Deregulated expression of some myomiRs results in pathological conditions. [15][16][17] miRNA encoding genes are transcribed as primary miRNA transcripts (pri-miRNAs) by RNA polymerase II. The mechanism by which pri-miRNAs are processed first to stem-loop structured miRNA precursors (pre-miRNAs) and then to mature miRNAs involves two sequential endonucleolytic cleavages operated by multiprotein complexes including the RNase III enzymes Drosha, in the nucleus, and Dicer, in the cytoplasm (reviewed in Krol et al 18 ).…”
mentioning
confidence: 99%